Stock Market Seasonals and Prespecified Multifactor Pricing Relations - Chang, Eric C.; Pinegar, J. Michael (Journal of Financial and Quantitative Analysis, 1990)
Despite nonstationarities in the factor betas and factor prices of the Chen, Roll, Ross (1986) multifactor model, investors are rewarded for bearing risks associated with the change in expected inflation and industrial production in non-January months; however, variations in these factors have opposite influences on stock prices. These findings may partially explain why several recent studies fail to detect a significant non-January risk premium in the stock market, but this evidence is only suggestive since theoretical and statistical difficulties prevent precise interpretations of specific pricing relations in the Chen, Roll, Ross model.